PENINGKATAN KEMAMPUAN GURU DALAM PENGELOLAAN PBM MELALUI PELAKSANAAN SUPERVISI AKADEMIK DENGAN PENDEKATAN KOLABORATIF DI SDN 007 TAMBUSAI UTARA SEMESTER II TAHUN PELAJARAN 2017/2018 - Karmono Karmono (STKIP Rokania Pasir Pangaraian, 2019)
This study aims to determine the implementation and improvement of teacher skills in the management of PBM through the implementation of academic supervision with a collaborative approach in SDN 007 Tambusai Utara in the second semester of 2017/2018 Academic Year especially in the aspects of managing teaching and learning activities. This type of research is school action research. The method and design of school action research is carried out by research procedures based on the principles of Kemmis and Taggart (1988: 10) which include the following activities: (1) planning (2) implementation of action, 3) observation (observation ), (4) reflection (reflection). The research subjects were teachers in SDN 007 Tambusai Utara in the first semester of the 2018/2019 Academic Year as many as 8 teachers. The technique of collecting data uses observation, and study documentation. The validity of the data using triangulation, namely Triangulation used in the study is data source triangulation and method triangulation. Data analysis using qualitative analysis. The results of the studyshowed an increase in the ability of teachers in the management of teaching and learning (PBM), where in the initial conditions there were no teachers who were able to arrange the management of teaching and learning processes (PBM) as evidenced by the low average scores obtained by teachers namely 49.50 and only included in the LESS category, in the first cycle it increased significantly and there were 3 teachers or 37.50% who were stated to be able to manage the teaching and learning process well, with a classical average value of 66, 83 and entered in the criteria for Enough and in the last cycle to be a teacher or 100%, as evidenced by the acquisition of a classical value of 80.17 in the Good value criteria. From the results of the study as explained above it can be concluded that the implementation of academic supervision with a collaborative approach at SDN 027 Semester II of the 2017/2018 Academic Year is proven to be able to improve the ability of teachers in PBM management